Microstructure and strength correlation of pure Al and Al-Mg syntactic foam composites subject to uniaxial compression - Lin, Yingfei; Zhang, Qiang; Zhang, Fuyang; Chang, Jing; Wu, Gaohui (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2017)
The microstructure and quasi-static compression of glass cenospheres/aluminum matrix syntactic foams (AMSFs) with three t/R ratio cenospheres (t/R=0.043, 0.052 and 0.064) and three different matrices (cp-Al, 5A03 and 5A06) were investigated. The compression strength and energy absorption of foams were found to increase with t/R ratio and Mg in matrix. The strengthening mechanisms were attributed to the nature properties of cenospheres and the thickness of high strength interfacial reaction MgAl2O4 forming. Two models were provided to predict the quasi-static properties of AMSFs considering the factors including physical properties of matrix and cenospheres, volume fraction of cenospheres, composition changing of matrix and thickness of interfacial reaction coating caused by interfacial reaction between matrix and cenopsheres. The predictions for peak stress, plateau stress, energy absorption capacity and specific energy absorption of AMSFs showed good agreement with experimental data. The Al-Mg syntactic foams in this study exhibited high specific energy absorption (56Jg−1) and specific plateau strength (94MPacm−3g−1).